Ketahanan Padi Lokal Asal Tabalong terhadap Empat Ras Penyakit Blas - Yashanti Berlinda Paradisa; A.Y. Perdani; Sri Indrayani (xxxx-xxxx, 2020)
Paradisa YB, Perdani AY, Indrayani S.  2020.  Resistance of Local Rice from Tabalong to Four Races of Blast disease. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One of the suboptimal land uses is for upland rice cultivation. However, the challenge in developing upland rice is disease attack, especially blast disease caused by Pyricularia grisea (Cooke) Sacc. The precaution that can be taken to reduce yield losses due to this disease is using resistant cultivars. A number of local rice germplasm is known to be resistant and tolerant to biotic and abiotic stress. So that local rice has the potential to be candidate parent crosses. This study aims to determine the level of resistance of local rice as candidate parent crosses especially local rice collected from Tabalong, South Kalimantan. Resistance information can be used to create resistant cultivars. This research was using eleven local rice (Jalapkin, Siam Rambung, Tambak Wangi, Mu'uy, Siang Tipung, Tipung, Mayas, Siam Sumut, Siam Jambul, Cantik Manis, and Lampung Gajah Putih). Research was performed at 18 days old plant and the treatment was repeated 4 times. Cultivar Asahan was used as resistant control, while Kencana Bali as susceptible control. Based on the study result, it is known that all of the local Tabalong rice has the potential to be used as parent crosses to create plant resistance except for Jalapkin and Tambak Wangi. However, Siam Rambung, Mu'uy, Tipung, Siam Jambul, Cantik Manis and Lampung White Elephant were more potential because resistant to 4 blast races